Participation of Farmer Leaders in Local and National Governance Structures: Will it Work? - Bawagan, Aleli B.; Cayabyab, Ana Angela T.; Lagos, Devralin T.; Obeciden, Victor G.; Vallejos, Celeste F.; Vallejos, Reginald S. (Philippine Journal of Social Development; Vol 5 (2013): Philippine Journal of Social Development, 2014)
-